Revisiting Academic Conferences in English Language Teaching (ELT) in Turkey - Ekoc, Arzu (JOURNAL LANGUAGE TEACHING & LEARNING, 2020)
The interest in the value of academic conferences in the field of ELT is steadily increasing in the last decade in Turkey. Despite the increased interest, conferences remain a relatively less researched area. Conference participation has become a demanding process and more and more academics have started to reconsider their participation and the benefits they get from the conferences. Therefore, a questionnaire was created concerning conference participants' opinions on the weak and strong points of ELT conferences in Turkey and 90 participants shared their views on what academic conferences are and what they might entail. The open-ended survey responses were analyzed qualitatively, with a focus on recurrent themes in participants' responses and other responses were analyzed quantitatively based on percentages and frequencies. The present study showed the ongoing need to increase the quality of papers presented in ELT conferences in Turkey. The findings can be fruitful for organizers and presenters. (C) Association of Applied Linguistics. All rights reserved
Keywords: ELT conferences; English Language Teaching; Academic; Higher Education; Teacher Development; COMMUNITIES; TEACHERS; Education & Educational Research